SUBJEK HUKUM DALAM PERSPEKTIF UNDANG-UNDANG TENTANG PERADILAN AGAMA - Diana Rahmi (Syariah: Jurnal Hukum dan Pemikiran, 2014)
Along with the enactment of Law No. 3 of 2006, Religious Court has been change related to law subject and principle of submission as well as added the Religious Court in resolving the disputes of Islamic economics. Non-Muslims or non-Islamic legal entity are allowed to be the subject of legal on dispute resolution in the Religious Courts. It is provided the legal relationship of civil underlies the Sharia. The presence of Article 1 paragraph 1 of Law No. 50 of 2009 is not to reduce the scope of the subject of law in the Law Religious Court previously, but this is related to law subject that have the meaning in narrow perspective, so that formulation of the notion in the article is need to be readjusted back in future.